Exercício físico e funções cognitivas em pacientes com doença de Alzheimer: associação com BDNF e APOE - Andrade, Larissa Pires de [UNESP] (2014)
The high incidence of patients with Alzheimer's disease and its consequent social and economic impact, they grow the effort of researchers interested in scientific research with the application of progressively more refined methods such as biological markers. These markers may help to understand the mechanisms by which physical exercise, as an alternative non-pharmacological treatment, can help slow the progression of the disease. In this perspective, this study is structured in the form of two articles. The first aimed to examine possible changes in serum Brain Derived Neurotrophic levels of Factor (BDNF) after a multimodal exercise program, four months duration in patients with clinical diagnosis of Alzheimer's disease (AD) in mild and moderate stages of disease. The study included 29 patients with AD were divided into subgroups according to the score of clinical dementia rating (CDR). Patients who were in the mild stage were classified as CDR 1 and the moderate stage, as CDR 2 Thus, the following subgroups were formed: 1.) CDR1 group exercise n = 10; 2) CDR 2 group exercise n = 4; 3) CDR1 group socializing n = 6; 4) CDR 2 group socializing n = 9. All patients participated in a battery of assessments, including the following tests: Modified Baecke Questionnaire for Older Adults, Mini Mental State Examination; Montreal Cognitive Assessment; Clock Drawing Test, Geriatric Depression Scale, and conduct assessment of serum BDNF levels. After four months of interventions was observed that patients who were in the moderate stage of the disease, who were part of the exercise group showed increased serum levels of BDNF. Showing that this protocol can be favorable for patients with these clinical conditions. The second article proposed to analyze the effects of physical exercise on serum BDNF and cognitive function of AD patients, carriers and non-carriers of the ε4 allele of apolipoprotein E (APOE). Thus, the following groups were formed: 1)...